Incidence of Uterine Bleeding Following Oral Anticoagulant Use in FDA's Sentinel System. Issue 3 (March 2021) - Anderson, Abby; Hou, Laura; Eworuke, Efe; Wong, Hui-Lee; Moeny, David; Huang, Ting-Ying; Gassman, Audrey
Abstract : (Abstracted from Am J Obstet Gynecol 2020; doi: 10.1016/j.ajog.2020.11.034) The aim of this study was to improve the understanding among clinicians of uterine bleeding (UB) events requiring intervention among women treated with an oral anticoagulant (OAC) therapy. The authors examined the incidence of UB events in the US Food and Drug Administration's (FDA's) Sentinel System, a database that comprised medical encounter and outpatient pharmacy claims data contributed by 17 public and commercial health insurers and integrated delivery networks.